Sphenopalatine ganglion stimulation for the treatment of trigeminal neuropathic pain - Sokal, Paweł; Kierońska-Siwak, Sara; Rusinek, Marcin; Jabłońska, Magdalena; Nehring, Antoni; Puk, Oskar; Palus, Damian; Jabłońska, Renata (Frontiers in Neurology, 2025)
IntroductionUnlike idiopathic trigeminal neuralgia, which can be treated with conventional neurosurgical methods such as microvascular decompression, radiofrequency rhizotomy of the Gasser ganglion, or stereotactic radiosurgery, trigeminal neuropathic pain (TNP) presents a major challenge for neurosurgeons. Injury to the trigeminal system resulting in chronic refractory pain can be treated with neuromodulation methods, such as peripheral nerve stimulation, motor cortex stimulation, or deep brain stimulation. Sphenopalatine ganglion (SPG) stimulation has been successfully applied in patients with cluster headaches and migraine. This study aimed to evaluate the response of patients with TNP to permanent percutaneous SPG stimulation.MethodsWe studied six patients treated with SPG stimulation for TNP. All patients had previously been treated with RF rhizotomy, microvascular decompression, or stereoradiosurgery without a satisfactory long-term therapeutic effect and had recurrent, mostly constant TNP. An electrode lead was implanted in the pterygopalatine fossa of all patients to stimulate the SPG under guidance of neuronavigation with an implantable pulse generator inserted after a two-week trial period.ResultsPreoperatively, the mean visual analog scale score was 9. Two weeks after the trial stimulation, it decreased to 3.6 in six patients. In four patients, the score further decreased to 3.0 after 6 months and 2.25 after 12 months, accompanied by an improvement in health status, as measured by the 36-Item Short Form Health Survey questionnaire. In two patients, the electrodes were externalized through eroded skin after 3 months, and stimulators were removed.DiscussionThe preliminary results of this pilot study are encouraging. Pain relief after the trial stimulation was found to be notable. The treatment procedure was safe, and the stimulation effect was durable. SPG stimulation is an attractive alternative to other neuromodulation methods.